Research progress of health anxiety (健康焦虑的研究进展) - YAO Min (姚敏); SHU Yusheng (束余声) (Journal of International Translational Medicine Limited, 2022)
Health anxiety is a continuous spectrum of symptoms from mild to severe. Persistent health anxiety can increase an individual's risk of developing depressive disorders, which can have serious physical and mental effects. This paper reviews the concept of health anxiety, main assessment tools, influencing factors and psychological intervention, and provides reference for further scientific development of nursing intervention measures of health anxiety and improvement of patients' quality of life. (健康焦虑是一种由轻到重的连续性的症状谱。持续存在的健康焦虑可能增加个体罹患抑郁障碍的风险, 对患者的身心造成严重的影响。本文从健康焦虑的概念、主要评估工具、影响因素及心理干预进行综述, 以期为今后进一步科学制定健康焦虑的护理干预措施以及提高患者的生活质量提供借鉴。)